Perceptions of Homeless Adults and Their Providers on Coping With the Impact of COVID-19 Pandemic on Mental Health, Substance Use, and Harm Reduction Services - Adeline M. Nyamathi; Lillian Gelberg; Darlene Lee; Nicholas Arce; Alexandria Patten-Jones; Kartik Yadav; Maniyah Goodwine; Mitra Alikhani; Maritas Yao; Alicia H. Chang; Benissa E. Salem (SAGE Publishing, 2022)
Adults experiencing homelessness experience a disproportionate burden of health disparities which has further exacerbated mental health, substance use, and coping during the COVID-19 pandemic. As limited data is available to understand the experience of adults experiencing homelessness and their health during this time, the purpose of this study was to explore how COVID-19 may have impacted their mental health, substance use, and ways of coping in this population. Using community-based participatory research, a community advisory board was established and remote individual interviews with 21 adults experiencing homelessness and 10 providers were conducted in Skid Row, Los Angeles. Using a qualitative, data analytic approach, the following major themes emerged: (1) Negative Impact of COVID-19 on Mental Health; (2) Negative Impact of COVID-19 on Limitation of Harm Reduction Services; and (3) Coping Strategies Utilized During the COVID-19 Pandemic. More research is needed to understand the impact of this pandemic on underserved communities.